1139 How effective is rituximab in nmo? a review of 50 patients. (1st December 2017) - Whittam, Dan; Hamid, Shahd; Mutch, Kerry; Linaker, Sam; Mawondo, Proude; Dodd, James; Jacob, Anu
Abstract : Introduction: In the UK, rituximab is a second line treatment for relapse prevention in neuromyelitis optica (NMO), after conventional immunosuppressant medications, primarily due to cost and lack of high level evidence. Method: Retrospective analysis of all patients of the UK NMO Service in Liverpool initiated on rituximab within the last 10 years. Results: 50 patients were identified from total cohort of 183. 36 were AQP4-IgG positive, 3 were MOG-IgG positive and 11 were seronegative. Median follow-up was 21 months on rituximab (range 2.1–112 months). Rituximab reduced the pre-treatment annualised relapse rate (ARR) by 83% (95% CI 73%–89%, p<0.001; Poisson regression model). Median ARR reduced from 1.1 (pre-rituximab) to 0 (post-rituximab). Kaplan-Meyer curves predict that 81% and 61% of patients remain relapse-free at 1 and 5 years respectively. At last follow up 42 patients remain on treatment. 14 patients experienced one or more relapses on rituximab and 7 relapses occurred despite adequate B-cell depletion. Conclusion: Rituximab is highly effective in preventing relapses in NMO. Considering the greatly disabling nature of NMO relapses there is an urgent need to commission it as a standard first line agent for NMO or for an RCT to establish unambiguous efficacy.